TOPONYMIC PHRASEOLOGICAL UNIT, LINGUISTIC THINKING AND DISCOURSE: RUSSIA, FRANCE AND ITALY - Sedykh, Arkadiy; Marabini, Alessandra; Stryzhnova, Mariana; Bolgova, Elena; Bolgova, Natalia (Revista Inclusiones, 2020)
The article studies phraseological units with a toponymic component on the material of linguistic and discursive manifestations in Russian, French and Italian linguistic cultures. National discourse in correlation with linguistic thinking is studied based on interpretative analysis of phraseology. In the context of the anthropocentric paradigm, the authors carry out a linguistic interpretation of systemic toponymic phraseological means. Being an integral part of spiritual culture, toponymic phraseological units exhibit certain features of verbalization in different languages and cultures. These features are determined by the subjective way in which speakers interpret the environment, which is undoubtedly of interest to linguistics and, in particular, to discourse studies. The differentiation of the national and cultural component of the phraseological unit, which is marked by a toponym, allows one to study phraseological units in terms of finding information on national culture, discourse and linguistic thinking in their semantics. A hypothesis is put forward that the semantics of phraseological units with a toponymic component reflects the relationship between any linguistic culture and the fundamental concepts of being and thinking, and the ways of toponymic phraseological verbalization could be viewed as elements of a nation’s linguistic self-identification.